3D Holey‐Graphene Architecture Expedites Ion Transport Kinetics to Push the OER Performance. Issue 22 (21st April 2020) - Wu, Pingwei; Wu, Jing; Si, Haonan; Zhang, Zheng; Liao, Qingliang; Wang, Xin; Dai, Fulong; Ammarah, Kausar; Kang, Zhuo; Zhang, Yue
Abstract: The kinetics process of heterogeneous catalysis involves several steps including adsorption, diffusion, and surface chemical reactions. Current studies generally aim at increasing active site amount and improving intrinsic activity. However, the ion diffusion kinetics at the electrode/electrolyte interface as a bottleneck has been rarely directly addressed. Here, a 3D holey‐graphene framework is demonstrated as a catalyst‐loading platform, with nanoscale holes that can be elaborately tuned via facile aqueous‐phase chemical etching. This enables the ions to be efficiently transported to deeply buried active sites to mitigate their insufficient supply. With systematical electrochemical investigations tuned by varied pore structures, a series of models from a simplified equivalent circuit to complicate realistic one are proposed to figure out the modulation rules of weakened electrochemical diffusion domination and identify the ion transport resistance as well. Moreover, given the inevitable negative effect on the conductivity of graphene skeleton by introducing nanoscale holes, the balance between the outside ion transport and the inside charge transport of electrode is highlighted. Such a protocol represents a synergistic modulation of catalytic performance from both the supply side (reactive ion transport) and the consuming side (active site), and provides striking information for the precise design of catalyst electrodes toward further pushing the oxygen evolution reaction performance limit. Abstract : Beyond traditional engineering strategies regarding intrinsic site activity and site amount, the reactive ion supply is herein strengthened to improve oxygen evolution reaction performance. This technique is based on expedited ion transport kinetics via precisely designed 3D holey‐graphene architecture as a catalyst‐loading platform, which indicates a synergistic modulation of catalytic performance from both supply side and consumer side.